2015
DOI: 10.1093/glycob/cwv034
|View full text |Cite
|
Sign up to set email alerts
|

Human sialic acid acetyl esterase: Towards a better understanding of a puzzling enzyme

Abstract: Sialic acid acetyl esterase (SIAE) removes acetyl moieties from the hydroxyl groups in position 9 and 4 of sialic acid. Recently, a dispute has been opened on its association to autoimmunity. In order to get new insights on human SIAE biology and to clarify its seemingly contradictory molecular properties, we combined in silico characterization, phylogenetic analysis and homology modeling with cellular studies in COS7 cells. Genomic and phylogenetic analysis revealed that in most tissues only the "long" isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Three novel genetic SIAE variants were identified in the patients of the study, all in heterozygous state and only in patients with aJIA ( Figure 1 ). The first alteration (c.1028A>C) was found in a patient with persistent antinuclear antibody- (ANA-) positive oJIA, resulting in the substitution of a neutral polar amino acid (glutamine) at the amino acid position 343 into a nonpolar amino acid (proline) (p.Q343P), within the catalytic portion of SIAE [ 25 ]. The second variant (c.1485C>A, p.Y495X) was a nonsense mutation in the C-terminal domain of SIAE, identified in a patient with RF-negative and ANA-positive pJIA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three novel genetic SIAE variants were identified in the patients of the study, all in heterozygous state and only in patients with aJIA ( Figure 1 ). The first alteration (c.1028A>C) was found in a patient with persistent antinuclear antibody- (ANA-) positive oJIA, resulting in the substitution of a neutral polar amino acid (glutamine) at the amino acid position 343 into a nonpolar amino acid (proline) (p.Q343P), within the catalytic portion of SIAE [ 25 ]. The second variant (c.1485C>A, p.Y495X) was a nonsense mutation in the C-terminal domain of SIAE, identified in a patient with RF-negative and ANA-positive pJIA.…”
Section: Resultsmentioning
confidence: 99%
“…This type of analysis represents an alternative approach to identify whether a particular nucleotide and/or amino acid change results in profound structural alterations and, therefore, might influence functionally relevant parts of a protein. In this context, we identified that p.Q343P mutation involves a highly conserved residue and might result in splice site changes by strengthening existing splice sites (according to the Mutation Taster tool); such an event might result in the loss of N-glycosylation sites at 401 and 422 residues and subsequently affect the catalytic activity of the enzyme, as glycosylation has been suggested a prerequisite to give rise to the biologically active form of the enzyme [ 25 ]. Considering the nonsense mutation p.Y495X, it is located in a partly conserved domain, despite the high degree of conservation of the 495 residue and results in a slightly truncated protein, with less than 10% of the full wild-type protein length being missing.…”
Section: Resultsmentioning
confidence: 99%
“…As CASD1 is not the only enzyme shown to be capable of acetylating GD3 29 our efforts focused on deacetylation of GD3 A by means of inducing expression of SIAE induction. The catalytic site of SIAE has been described previously, allowing us carry out a functional study using this enzyme and a catalytically dead mutant SIAE S127A 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…SIAE in its active form is a glycoprotein with a molecular weight of 62 kDa 42 . When SIAE and S127A were expressed in the RES256 cell line, the expression appeared to be somewhat different, even when considering that total protein loading was less for S127A.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody staining shows that Cse is found diffusely throughout the cytosol, where it is thought to remove 9- O- and 7- O -acetyl groups to recycle the Sia for reuse in glycosylation (12). Despite the reports of distinct protein expression in mouse tissues, bioinformatic analysis of RNA expression in human cells and tissues show mRNA corresponding to the Lse form of SIAE and none responding to the Cse form (13). It is therefore still unclear how these two isoforms are regulated in humans or other animals, whether their expression relates to CasD1, or what controls the levels and locations of 9- O - and 7,9- O -Ac expression.…”
Section: Introductionmentioning
confidence: 87%